Presupposition and Othering in a Dystopian Novel Red Rising - Leonandho, Muhammad Adam Akbar; Ariyanti, S.S., M.Pd., Lisetyo; Setiawan, M.A., Ph.D., Prof. Slamet; Hartanti, S.Pd., M.EIL, Lina Purwaning (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
The researcher has analyzed the concept of Colonialism Discourse in a dystopian novel titled Red Rising using qualitative method to gather the data. Othering is used to explain the colonialism discourse in the novel. The researcher used Focault (1990) theory to describe how othering happened in the novel’s background story. Beside othering, presupposition is also used to gather the data. For the presupposition, the researcher used Yule (1996) theory which has six types of presupposition. The purpose of this research is how Othering which is part of colonialism discourse could happened in a dystopian novel which is a new genre in this modern era. By using presupposition to understand the othering concept in the novel, this research focused on the meaning of the utterances using the types of presupposition and how those presupposed meaning can give the pragmatics function in the concept of Othering. The researcher found that presupposed meaning of the utterances could help to determine the othering expression based on the context in the story. The researcher found that the most used presupposition is existential because it contains adjective pronouns to emphasize the characters’ thoughts or feeling to the readers. Other types of presupposition are existed in the story being viewed as the way the characters showed their identity as an individual in the society. As a dystopian novel which has some elements of colonialism discourse, Red Rising often uses humiliation to mock or underestimate other colors society. The researcher found that the othering expression used in this novel depicts the concept of colonialism literature about the oppressing leader in one social hierarchy. The totalitarian leader has created label to identify each individual with their own position and authority to gain easy access to control everything in the social system. In a word, othering has its own role in the colonized society by showing how the system of social hierarchy works in the story.